The potential impact data of Tylosin and Enrofloxacin veterinary antibiotics on germination and accumulation in barley seed as a forage crop and good dietary sources using LC/MS-MS - Ahmed Abou, Elezz (2019)
In this study, the phytotoxic effects caused by the exposure to five different concentrations of two veterinary antibiotics (Tylosin, and Enrofloxacin) that are commonly used for the treatment of farm animals as antibacterial agents were considered. The impact of antibiotic residues was evaluated on the germination percentage, accumulation, and seedling elongation of the barley seeds using Petri dishes under controlled environmental conditions. The treatments were distributed randomly using Completely Randomized Design (CRD). The germination percentage was significantly inhibited with the increasing Enrofloxacin dose concentrations, while, it was to some extent on the contrary in the case of Tylosin, where seed germination was enhanced as a result of increasing Tylosin concentrations.Liquid chromatography-tandem mass spectrometry LC/MS-MS was used to detect and quantify the uptake dosage after drying and extracting the antibiotic compounds from the seedling.